What is a Person? And Why it Matters in Religious Ethics. Issue 1 (March 2014) - Smith, Christian
Abstract Here I respond to four critics of my book, What Is a Person?, seeking to find areas of common ground and crucial disagreement. Most importantly, I explore the question of whether all human knowledge is conceptually mediated, acknowledging that, no, indeed, there are likely forms of experiential knowledge that are purely and directly acquired without conceptual mediation.